2006
DOI: 10.1111/j.1745-459x.2006.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

SENSORY PROPERTIES OF WILD AND AQUACULTURED SOUTHERN FLOUNDER (PARALICHTHYS LETHOSTIGMA)

Abstract: There is considerable interest in the aquaculture of southern flounder, Paralichthys lethostigma, because of its worldwide market appeal, high market value and ability to grow in fresh or brackish water. This study was conducted to identify and define sensory properties of wild (WF), freshwater farm-raised (FFF) and saltwater farm-raised (SFF) southern flounder. In addition, consumer acceptance of these three sources of southern flounder was determined. A defined sensory lexicon for southern flounder (appearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 16 publications
(23 reference statements)
2
31
1
Order By: Relevance
“…Panelists evaluated and discussed several types of poached commercially purchased white fish (catfish, cod, summer flounder and tilapia). A previously developed sensory lexicon for southern flounder which included 10 flavors and 5 basic tastes was used for evaluation (Drake et al. 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Panelists evaluated and discussed several types of poached commercially purchased white fish (catfish, cod, summer flounder and tilapia). A previously developed sensory lexicon for southern flounder which included 10 flavors and 5 basic tastes was used for evaluation (Drake et al. 2006).…”
Section: Methodsmentioning
confidence: 99%
“…2008a), barramundi (Percival et al. 2008) and southern flounder (Drake et al. 2006) have also been found to exhibit this earthy/musty off‐flavor.…”
Section: Introductionmentioning
confidence: 99%
“…Drake et al (2006) however found a greater number of North Carolina consumers prefer saltwater farm-raised seafood. The conjoint choice questions in our survey measured preferences and WTP for farm-raised vs. wild-caught fish products, but additionally participants were directly asked ''for seafood, which of the following types do you most prefer?''…”
Section: Aquaculture Vs Wild-caught Seafood Preferencesmentioning
confidence: 95%
“…Demographic data from respondents have been used as explanatory variables in previous seafood market research (Gempesaw II et al, 1995, Consumer Choice Between Aquaculture Fish and Wild-Caught Seafood in Hawaii 141 Hanson et al, 1995, Engle & Kouka, 1995, Johnston et al, 2001, Harrison et al, 2002, Jaffry et al, 2004, Drake et al, 2006, Johnston & Roheim, 2006Quagrainie, 2006;Quagrainie & Engle, 2006). The effect of consumer socioeconomic factors on seafood preferences are not directly analyzed in this study, the effect which can typically be analyzed by creating interacted terms between consumer characteristic variables and product attribute variables.…”
Section: Profile Of Survey Respondentsmentioning
confidence: 99%
See 1 more Smart Citation